THE EFFICIENCY OF TECHNIQUE OF DOUBLE ARCHES BY THE TREATMENT OF PATIENTS WITH IMPACTED PERMANENT CANINES - S. V. Dmitrienko; D. A. Domenyuk; A. V. Kokareva; D. S. Dmitrienko; M. A. Agashina (Современная наука и инновации)
As a result of examination and treatment of patients of the first period of mature age with impacted canines revealed the efficiency of the application of technique of double arches. As the main arc it was used a steel metal arc with rectangular section preformed to suit the individual size of the dental arches and morphometric parameters of the cranio-facial complex. The second, supporting nitinol arc, was included in the segment of the dental arc, with fixation to the brackets located on the impacted canine and 2-3-rd teeth on either sides of it. The diameter of the nitinol arc determined by the clinical picture and the magnitude of the load on the tooth, which did not exceed 30-40 gramms